Artificial intelligence and labour law - Bernd Waas (Hugo Sinzheimer Institut für Arbeits- und Sozialrecht (HSI), Hans-Böckler-Stiftung, 2022)
[Introduction:] Today, we encounter artificial intelligence (AI) applications at every turn, albeit often unnoticed. AI research has developed at a rapid pace. What seemed almost unthinkable yesterday may already be an integral part of everyday life tomorrow. AI is also becoming more and more prevalent in companies. AI applications offer firms but also their employees many opportunities; one need only think of workers' health protection. At the same time, however, the development brings considerable risks and challenges. It is these risks and challenges in particular that this study addresses. The core questions are: What does AI mean for the protection of employees? What challenges do individual labour law and co-determination face? The fact that the study's focus is on the risks and not on the opportunities should not be misunderstood. Since the paradigm of labour law is the protection of the employee - typically the weaker party - it should not be surprising if we focus on the question of whether and to what extent this is affected by AI. The following sections, after a look at the basics (B.), will first look at the use of AI in working life (C.). This is already very advanced, especially in the USA. Initiatives will then be presented that focus in particular on the development of ethical principles for AI, but also in part on the regulation of AI. The analysis begins at the international level (D.), where the activities of the Council of Europe deserve special attention, then moves to the level of the European Union (E.), where the European Commission's proposal for an "AI law" will be discussed, and finally leads to the level of Germany (F.), where - in the form of some regulations of the Betriebsrätemodernisierungsgesetz - the first legislative activities have already been recorded. This is followed by a closer look at individual problem areas in labour law (G.). The study closes with a brief conclusion (H.).
Keywords: 340